2008
DOI: 10.1111/j.1600-051x.2008.01313.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of matrix metalloproteinase‐1 −1607 1G/2G polymorphism in a Turkish population with periodontitis

Abstract: On the basis of the results, no significant association is found for the MMP-1 -1607 1G/2G polymorphism with susceptibility to periodontitis. Moreover, smoking status did not seem to affect this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
1
16
0
5
Order By: Relevance
“…[40][41][42][43][44] These inconsistent data may be partly explained by the different clinical, methodological and statistical settings, as well as by variances in TNF genotype distributions within distinct races and /or populations. 45,46 In this study, we detected a statistically significant correlation between the genetic variant of TNF-α (-308G) and the occurrence of GAgP ( Table 2). The frequency of the AG genotype of TNF-α polymorphisms is higher in GAgP patients in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 54%
“…[40][41][42][43][44] These inconsistent data may be partly explained by the different clinical, methodological and statistical settings, as well as by variances in TNF genotype distributions within distinct races and /or populations. 45,46 In this study, we detected a statistically significant correlation between the genetic variant of TNF-α (-308G) and the occurrence of GAgP ( Table 2). The frequency of the AG genotype of TNF-α polymorphisms is higher in GAgP patients in comparison with healthy controls.…”
Section: Discussionsupporting
confidence: 54%
“…23 consequently, we suggest that there is no association between MMP-1 (-1607) polymorphism and susceptibility to CP in smoking patients. An in vitro study 24 concluded that the MMP-1 (-1607) polymorphism has functional significance in controlling the level of transcription and protein production of MMP-1 in periodontal ligament cells, which implies that subjects with CP with the 2G allele may have severe degradation of the extracellular matrix.…”
mentioning
confidence: 63%
“…[20][21][22] However, the lack of association between MMP-1 and CP suggests that the increase in mRNA transcription might not necessarily lead to the increase in enzyme activity on the extracellular matrix, as confirmed in other populations. 19,23,25 …”
mentioning
confidence: 99%
“…33 More recently, two studies in Turkish populations showed different results. Pirhan et al 50 reported an association of the MMP1*2G allele with severe periodontitis, and no association was found of this allele with periodontitis in the study by Ustun et al 51 These discrepancies may reflect the involvement of variable combinations of risk alleles in different populations, confounding factors such as genetic admixture, regional differences in gene frequencies, geneenvironment interactions, and a poor sample selection of extreme phenotypes. 52 In fact, we observed that most studies considering extreme phenotypes (especially severe diseases) were able to detect an association between the MMP1-1607 gene polymorphism and CP.…”
Section: Discussionmentioning
confidence: 95%